Tinkers - Harding, Paul, frey50 (New York : Bellevue Literary Press, 2009)
On his deathbed, surrounded by his family, George Washington Crosby's thoughts drift back to his childhood and the father who abandoned him when he was twelve.
Keywords: Reminiscing in old age; Identity (Psychology) in old age; Dementia -- Patients; Fathers and sons; Psychological fiction